2020
DOI: 10.1042/cs20190584
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Nox4/AMPK/mTOR signaling axe in adipose inflammation-induced kidney injury

Abstract: Diabetic kidney disease is one of the most serious complications of diabetes worldwide and is the leading cause of end-stage renal disease. While research has primarily focused on hyperglycemia as a key player in the pathophysiology of diabetic complications, recently, increasing evidence have underlined the role of adipose inflammation in modulating the development and/or progression of diabetic kidney disease. This review focuses on how adipose inflammation contribute to diabetic kidney disease. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 194 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…As Nox4/AMPK/mTOR signaling has been reported to be implicated in diabetic kidney disease ( 21 ), we hypothesized that the AMPK/mTOR signaling might be implicated in Nox4-mediated regulation of HG-induced injury. HK-2 cells were transfected with si-Nox4 and treated with HG in combination with the AMPK activator AICAR or the mTOR activator propranolol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Nox4/AMPK/mTOR signaling has been reported to be implicated in diabetic kidney disease ( 21 ), we hypothesized that the AMPK/mTOR signaling might be implicated in Nox4-mediated regulation of HG-induced injury. HK-2 cells were transfected with si-Nox4 and treated with HG in combination with the AMPK activator AICAR or the mTOR activator propranolol.…”
Section: Resultsmentioning
confidence: 99%
“…Nox4 has been reported to be upregulated in high glucose-treated renal tubular epithelial cells, and it regulated high glucose-induced cell apoptosis through the Notch signaling ( 20 ). The Nox4/AMPK/mTOR signaling play important roles in diabetic renal disease ( 21 ). Puerarin ameliorated diabetic renal injury by inhibiting the expression of Nox4 in podocytes, indicating that Nox4 could be targeted for DN treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that CTSK could promote tumor cells proliferation via mTOR signaling pathway 32,33 . The mTOR signaling pathway, as a critical intracellular pathway, is involved in cell proliferation, growth, apoptosis, differentiation, in ammation, and survival 34,35 . p70S6K and 4EBP1 are key downstream substrates of mTOR1.…”
Section: Discussionmentioning
confidence: 99%